Comparative analysis of financial risks towards financial stability of Islamic and conventional banks in GCC countries - Al-Wesabi, Hamid Abdulkhaleq Hasan (2022)
Dependency of GCC countries on oil sector revenues exposes them to financial risks. This study aims to examine the banks’ financial stability and its determinants from financial risks perspective, to highlight the resilience of Islamic and conventional banks in the wake of economic vulnerabilities. Financial risks affect the banking systems through deterioration of liquidity and asset quality as GCC financial systems are more reliant on banks than the non-banking institutions. This study shows the relationship between financial stability of the banks (measured by Z-Score Index and risk adjusted returns on assets and equity), and the financial risks as independent variables (namely: macroeconomic, industry-specific, and bank-specific variables). The method employed is panel cointegration analysis (Pedroni’s Method) and panel FM-OLS, D-OLS and FGLS estimation covering 2000 to 2017. The study also compares the financial stability and resilience, liquidity, capital, and efficiency between Islamic and conventional banks for the periods before, during and post financial crisis. The findings affirmed that there are differences, in the forms of impact, direction and significance of financial risks and banks’ financial stability, between Islamic and conventional banks, in terms of stability, inflation, crisis period impact, political instability, competition, financial sector development, credit risk, liquidity, capital and diversification. It shows the nature of banks matters to realize more financial stability and soundness against the effects of financial risks exposure. The findings also shed some light on whether similar policy ramifications can be implemented to mitigate risks in order to maintain the soundness and resilience of both Islamic and conventional banks. Thus, Central Banks and regulatory authorities should implement their policies accordingly, to avoid instability and future financial crises. Once the banking system is more resilient, economy of GCC countries will be less vulnerable to systemic risks of future financial crises and thus the economic development will be more sustainable.